(untitled) (INNOVATIVE ECONOMY, 2020)
Bachynskyi V.I., Pomulieva V.M. ACTUAL ASPECTS OF VAT ACCOUNTING FOR THE PURCHASE OF GOODS Purpose. The aim of the article is highlight the main aspects and current problems of VAT accounting in the purchase of goods and the search for effective solutions for its accounting. Methodology of research. General scientific and specific methods are used in the study: logical analysis, systematic approach, synthesis, induction and deduction, generalization (in the study of current norms and regulations on accounting regulation and display methods, accounting features), abstract and logical (in generalization of theoretical provisions and formation conclusions and suggestions). Findings. The current problems of VAT accounting for the purchase of goods are substantiated. It is proposed to use analytical accounts to reflect the value added tax when purchasing goods. The problematic aspects of the need to accrue VAT liabilities in the case of purchase of goods, their accounting are identified. Proposals have been formed for the use of analytical accounts to account for VAT liabilities. Emphasis is placed on ambiguous interpretations of tax norms and the opinion is expressed on the need for legislative and regulatory regulation of certain issues of value added tax accounting. Originality. Proposals have been developed to improve the accounting of value added tax when purchasing goods, which will ensure the possibility of forming the accounting policy of enterprises on VAT accounting and will contribute to the reliability of accounting, tax reporting and correctness of calculations with the budget. Practical value. The results of the study and the developed proposals can be used by VAT payers in developing the methodology of VAT accounting in their accounting policies and in accounting for value added tax, as well as implemented through legislative changes. Key words: Tax Code, value added tax, accounting, tax credit, tax liabilities, tax invoice.